(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
This article reflects and problematizes the issue of menstruation in the town of Santa Rosa, La Pampa in relation to a series of testimonies on menstruation, in the framework of a menstrual activism by the writer, promoting and dedicating to communication and integral menstrual health. In addition, emerges as an edge of the thesis “Feminist activism in social networks: the case of EcoFeminita and its campaign “MenstruAcción”, research in progress that is being carried out in 2022. From a main introduction, the arguments of the topic will be detailed as well asthe importance of investigating it from the communication. In a second part the results obtained by the data collection will be presented, and ultimately this information will be systematized; to conclude the section with a final reflection.